Substrate stress relaxation regulates monolayer fluidity and leader cell formation for collectively migrating epithelia - Frank Charbonier; Junqin Zhu; Raleigh Slyman; Cole Allan; Ovijit Chaudhuri (Proceedings of the National Academy of Sciences, 2025)
Collective migration of epithelial tissues is a critical feature of developmental morphogenesis and tissue homeostasis. Coherent motion of cell collectives requires large-scale coordination of motion and force generation and is influenced by mechanical properties of the underlying substrate. While tissue viscoelasticity is a ubiquitous feature of biological tissues, its role in mediating collective cell migration is unclear. Here, we have investigated the impact of substrate stress relaxation on the migration of micropatterned epithelial monolayers. Epithelial monolayers exhibit faster collective migration on viscoelastic alginate substrates with slower relaxation timescales, which are more elastic, relative to substrates with faster stress relaxation, which exhibit more viscous loss. Faster migration on slow-relaxing substrates is associated with reduced substrate deformation, greater monolayer fluidity, and enhanced leader cell formation. In contrast, monolayers on fast-relaxing substrates generate substantial substrate deformations and are more jammed within the bulk, with reduced formation of transient lamellipodial protrusions past the monolayer edge leading to slower overall expansion. This work reveals features of collective epithelial dynamics on soft, viscoelastic materials and adds to our understanding of cell–substrate interactions at the tissue scale.